Upaya Meningkatkan Keterampilan Menulis Teks Persuasi dengan Menggunakan Media Poster di MTs Negeri 4 Bantul - Suratmi Suratmi (Jurnal Pendidikan Madrasah, 2023)
This study aims to improve the ability to write persuasion texts using poster media. This study used action research methods carried out in two cycles. Each cycle consists of four stages, namely planning, execution, observation, and reflection. Data collection techniques use written tests, observations, field notes, and photo documentation. The research instrument uses observation sheets, persuasion text writing skills assessment sheets and photo documentation. The subject of the study was a student of grade VIII.D MTs Negeri 4 Bantul Even Semester of the 2021/2022 Academic Year. The results showed that learning using poster media can increase students' activeness and skills in writing persuasion texts, both in terms of process and product. This can be seen in the results of the persuasion text writing test from the pre-action stage to cycle II increased from 46% to 85%. Poster media is one of the writing learning media that can increase the activeness and skills of students writing persuasion texts.